2018
DOI: 10.1016/j.taap.2018.08.015
|View full text |Cite
|
Sign up to set email alerts
|

PFOS-induced excitotoxicity is dependent on Ca2+ influx via NMDA receptors in rat cerebellar granule neurons

Abstract: Perfluoroalkyl acids (PFAAs) are persistent compounds used in many industrial as well as consumer products. Despite restrictions, these compounds are found at measurable concentrations in samples of human and animal origin. In the present study we examined whether the effects on cell viability of two sulfonated and four carboxylated PFAAs in cultures of cerebellar granule neurons (CGNs), could be associated with deleterious activation of the N-methyl-d-aspartate receptor (NMDA-R). PFAA-induced effects on viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 61 publications
(87 reference statements)
1
20
0
Order By: Relevance
“…In our unpublished studies (manuscript under review) we found that the POP mixture at 500x fold human blood levels and PFOS at 20 mM, in a corresponding concentration, induced excitotoxicity via the involvement of N-methyl-D-aspartate receptor (NMDA-R) in cultures of chicken cerebellar granule neurons (CGNs). A similar result has been observed by our group using the same POP mixture at concentrations from 500x, and PFOS in rat as well as in chicken CGNs (Berntsen et al, 2018(Berntsen et al, , 2020. PFOS-induced neurotoxicity has also previously been studied in PC12 cells (Li et al, 2017;Slotkin et al, 2008).…”
Section: Introductionsupporting
confidence: 86%
“…In our unpublished studies (manuscript under review) we found that the POP mixture at 500x fold human blood levels and PFOS at 20 mM, in a corresponding concentration, induced excitotoxicity via the involvement of N-methyl-D-aspartate receptor (NMDA-R) in cultures of chicken cerebellar granule neurons (CGNs). A similar result has been observed by our group using the same POP mixture at concentrations from 500x, and PFOS in rat as well as in chicken CGNs (Berntsen et al, 2018(Berntsen et al, , 2020. PFOS-induced neurotoxicity has also previously been studied in PC12 cells (Li et al, 2017;Slotkin et al, 2008).…”
Section: Introductionsupporting
confidence: 86%
“…For example, PFAS could act on different neurotransmitter receptors, such as glutamate receptors, thereby masking the inhibition of the GABA A receptor. This idea is supported by research that showed that PFOS induces NMDA receptor mediated excitotoxicity 59 . Toxicity results of a high influx of extracellular Ca 2+ , which in its turn over-activates the NMDA receptor.…”
Section: Discussionmentioning
confidence: 87%
“…In a follow-up study, Berntsen et al (2018) showed that excitotoxicity induction by PFOS in CGNs is likely due to over-activation of the N-methyl-D-aspartate receptor (NMDA-R) and excess influx of Ca 2+ . Channel blockers (memantine and MK-801) also showed some effects against PFHxS-induced reductions in viability.…”
Section: In Vitro Studiesmentioning
confidence: 99%